Placenta Accreta Spectrum: Conservative Management and Its Impact on Future Fertility. Issue 4 (18th October 2021) - Abbas, Riwa A.; Nassar, Anwar H.
Abstract : Abstract: Placenta accreta spectrum is a complication of pregnancy, which poses a great risk on maternal health. Historically, hysterectomy was the modality of treatment of such condition, but an approach towards a more conservative management has been in the light recently. This includes several methods with varying rates of success and complications. Expectant management is effective in up to 78%–80% of the cases. The extirpative method is associated with a high risk of postpartum hemorrhage. The success of the one-step conservative procedure depends on the degree of placental invasion, and the triple-P procedure appears to be successful but requires and interdisciplinary approach. Adjuvant treatment options can be tailored according to individual cases, and these include methotrexate injection, uterine devascularization and hysteroscopic resection of retained placental tissues. Follow up after conservative management is crucial to detect complications early, and it can be done by ultrasound, Doppler examination, and trending β human chorionic gonadotropin levels. Conservative management of placenta accreta spectrum can preserve future fertility but should only be done in hospitals with enough experience as it carries a high risk of maternal complications. In the future, more research should be directed to achieve clear guidelines regarding this topic.